Körpermodifikationen und leibliche Erfahrungen in der Adoleszenz Eine feministisch-phänomenologisch orientierte Studie zu Inter-Subjektivierungsprozessen - Ganterer , Julia (Schriftenreihe der ÖFEB-Sektion Sozialpädagogik, 2019)
In her interdisciplinary work, Julia Ganterer examines the subject of body and inter-subjectivity of young adolescents from a socio-educational, body-phenomenological and gender-critical perspective. With the help of interviews, she examines the context in which the body shapes, gender constructions and inter-subjectivization processes of adolescents stand and traces how social conditions are inscribed in body practices.